Effect of rGO on the mechanical strength, hydration and micromorphology of cement incorporated silica fume. (20th September 2021) - Zhang, Qian; Sun, Hao; Liu, Wangang; Zhou, Zonghui; Yuan, Lianwang; Ren, Zunchao; Geng, Dongjian; Wang, Jinbang; Cheng, Xin
Highlights: rGO effectively enhances the mechanical strength of cement based materials. rGO accelerates the hydration and optimizes the pore distribution of cement based materials. The enhancement of strength mainly attributes to the regulation and reinforcement on microstructure. Abstract: Reduced graphene oxide (rGO) exhibits extensive prospects in modifying the strength, durability, electrothermal or electromagnetic properties of cement composites. However, there are still controversial conclusions about rGO. This work revealed the influence mechanism of rGO on the strength, hydration and micromorphology of cement composites. Results demonstrated that rGO effectively enhanced the strength of mortar. The 1-, 3-, 28-day flexural and compressive strength of specimens improved by 6.6% and 22.6%, 12.5% and 21.3%, 24.3% and 30.3% respectively. TGA quantitative characterization showed rGO had narrow promotion on hydration. With 0.08% rGO, the CH and C-S-H content increased by 4.76% and 0.67% than samples without rGO. Whereas rGO effectively reduced the cumulative pore volume, optimized the pore size distribution. The total porosity decreased by 10.3%, and the percentage of harmful pore decreased by 22.5%. Thus, the strength enhancement mainly attributed to the regulation of microstructure and cross-linking effect of rGO, which observed by SEM-EDS.